Prototype of an axial flux permanent magnet generator for wind energy systems applications - Ferreira, Ângela P. (2007)
Small scale wind power applications require a cost effective and mechanically simple generator in order to be a reliable energy source. The use of direct driven generators, instead of geared machines, reduces the number of drive components, which offers the opportunity to reduce costs and increases system reliability and efficiency. For such applications, characterized by low speed of rotation, the axial flux permanent magnet generator is particularly suited, since it can be designed with a large pole number and high torque density. This paper presents a double-sided axial flux permanent magnet low-speed generator, with internal rotor and slotted stators. Such a structure gives a good compromise between performance characteristics and feasibility of construction. Test results obtained from the prototype are reported.